Cultural Taxation: The Experiences of Māori Teachers in the Waitaha (Canterbury) Province of New Zealand and their Relevance for Similar Australian Research - Torepe, Toni K.; Manning, Richard F. (The Australian Journal of Indigenous Education, 2017)
This article draws on data from a research study (Torepe, 2011) that investigated the lived experiences of six Māori teachers who recently graduated from the Hōaka Pounamu (Graduate Diploma in Immersion and Bilingual Teaching) course at the University of Canterbury, New Zealand. The primary objective was to gain a deeper understanding of the lived experiences and various challenges confronting this group of experienced Māori language teachers working in English-medium, state-funded schools. This article describes the qualitative research methodology that was underpinned by a Kaupapa Māori narrative research philosophy. It then explains why the study's findings support and strengthen those of previous studies conducted in Australia. Most notably, they draw attention to the concept of cultural taxation and the Crown's principles for action on the Treaty of Waitangi. Given the large number of Māori children attending Australian schools and similar challenges confronting Indigenous Australian teachers, this research will be of interest to an Australian audience.